The Differential Effects of Intermediate Complications with Postoperative Mortality. Issue 3 (March 2013) - Borgi, Jamil; Rubinfeld, Ilan; Ritz, Jennifer; Jordan, Jack; Velanovich, Vic
Most attempts at understanding perioperative mortality have been based on assessing individual patient risk factors, types of operations, and hospital characteristics. The hypothesis of this study is that there is a relationship between postoperative mortality and postoperative complications; therefore, understanding this relationship may provide a basis for prevention and rescue. Using the 2007 SemiAnnual National Surgical Quality Improvement Program Report, we obtained data for each reporting hospital's rates of observed mortality, overall observed morbidity, observed cardiac, respiratory, renal complications, venothromboemoblic events (VTEs), surgical site infections (SSIs), and urinary tract infections (UTIs). Simple and multiple linear regression analyses were done comparing absolute rate of observed mortality with absolute rate of observed morbidity and each morbidity group. One hundred ninety-seven hospitals were included in the study. There were statistically significant associations between observed mortality rates and observed morbidity rates, cardiac complications, respiratory complications, and VTE rates. Renal complications, SSIs, and UTIs showed no statistically significant association with observed morbidity. This study demonstrates that rates of observed morbidity, especially cardiac, respiratory, and VTE complications, are associated with observed mortality. These findings suggest that care providers should focus efforts at prevention and rescue of cardiac, respiratory, and VTE complications.